Temperature response of ex-situ greenhouse gas emissions from tropical peatlands: interactions between forest type and peat moisture conditions - Sjögersten, S.; Aplin, P.; Gauci, V.; Peacock, M.; Siegenthaler, A.; Turner, B.L. (Elsevier, 2018)
Climate warming is likely to increase carbon dioxide (CO2) and methane (CH4) emissions from tropical wetlands by stimulating microbial activity, but the magnitude of temperature response of these CO2 and CH4 emissions, as well as variation in temperature response among forest types, is poorly understood. This limits the accuracy of predictions of future ecosystem feedbacks on the climate system, which is a serious knowledge gap as these tropical wetland ecosystems represent a very large source of greenhouse gas emissions (e.g. two-thirds of CH4 emissions from natural wetlands are estimated to be from tropical systems). In this study, we experimentally manipulated temperatures and moisture conditions in peat collected from different forest types in lowland neotropical peatlands in Panama and measured how this impacted ex-situ CO2 and CH4 emissions. The greatest temperature response was found for anaerobic CH4 production (Q10 = 6.8), and CH4 consumption (mesic conditions, Q10 = 2.7), while CO2 production showed a weaker temperature response (Q10 < 2) across the three moisture treatments. The greatest temperature response of CO2 production was found under flooded oxic conditions. Net emissions of CO2 and CH4 were greatest from palm forest under all moisture treatments. Furthermore, the temperature response of CH4 emissions differed among dominant vegetation types with the strongest response at palm forest sites where fluxes increased from 42 ± 25 to 2166 ± 842 ng CH4 g−1 h−1 as temperatures were raised from 20 to 35 °C. We conclude that CH4 fluxes are likely to be more strongly impacted by higher temperatures than CO2 fluxes but that responses may differ substantially among forest types. Such differences in temperature response among forest types (e.g. palm vs evergreen broad leaved forest types) need to be considered when predicting ecosystem greenhouse gas responses under future climate change scenarios.